Short and Effective: A Reasoned Proposal for Organizational Climate Measurement - Ramos, Valentina; Ramos-Galarza, Carlos; Pazmiño, Pablo; Tejera, Eduardo (Emerging Science Journal, 2024)
Generally, organizational climate research does not focus on the work environment because the mindset and emotions of employees are often mistaken for organizational culture. Additionally, surveys to evaluate the organizational climate tend to be long, and therefore, organizational climate studies are conducted only once a year—that too if an organization is concerned about its employees. This research proposes a methodology to evaluate organizational climate; the methodology has the following characteristics: it is a short evaluation named “pulse”; it is oriented toward specific elements of culture that influence the organizational climate and its variability; and it considers organizational contexts. The study was conducted in three organizations encompassing three sectors (N=3,331 employees). The survey included three questions regarding employees’ feelings and climate perception at the individual, group, and organizational levels. Additionally, it had 56 questions related to the elements of organizational culture, grouped into six components after an exploratory analysis: Structure, Recognition, Leadership, Accountability, Work Team, and Ethics. The results showed significant differences between organizations based on the organizational climate perception, its strength, and the behavior of the variables associated with the organizational culture that impacts the climate. Additionally, cultural elements were reduced because of their relationship with the organizational climate. This research suggests that organizational climate studies should be conducted for specific organizational contexts. Additionally, it proposes a methodology to reduce the duration of organizational climate studies by focusing on specific cultural dimensions associated with the climate, which can be applied longitudinally throughout the year to monitor climate changes. Doi: 10.28991/ESJ-2024-08-05-09 Full Text: PDF